Il nuovo romanzo La narrativa d'avanguardia nella prima fase della postmodernità (1953-1973) - FASTELLI, FEDERICO (Premio Ricerca «Città di Firenze», 2013)
The systematic examination of the fluctuations in the definition of the terms "neo-avant-garde" and "post-modern" is at the base of this study, which therefore evolves through the comparative analysis of different contexts, with particular reference to the Italian one (Group 63) and to the French one (Nouveau Roman). Thus, an articulated framework of deeply intertwined narrative experiences emerges, making a valid and completely original contribution to the discussion on well-established historical categories within the literary history and critical theory of the second half of the 20th century.